Tropical rainforest typology and conversion effects on river water quality Sarawak, Malaysia. - Rosli, Noraini (2017)
Despite various efforts taken by Malaysia Government, water quality degradation in Malaysian rivers remains unsolved. There is an urgent need to conduct detail studies on water quality condition from various land use of Malaysia. This study was conducted in response to environmental problems of Malaysia and its conversions effect on river water quality. Thus, the objectives of this study were to: (i) determine the impacts of converted forest on water quality; (ii) determine water quality status of several tropical forest types and forest conversions; (iii) derive pollutant concentration of the river water; and (iv) identify the most influence variables cause deteriorating of water quality of forest land uses. A total of 756 water samples were collected from upstream, middle stream and downstream of river at each study area. Water quality was interpreted using National Water Quality Standard and Water Quality Index developed by Department of Environment Malaysia and analysis implemented according to Standard Methods for the Examination of Water and Wastewater by APHA was followed. The physico-chemical variables of river water of dam (Bakun), oil palm plantations (Lawas II) and agricultural area (Lawas III) were found under Class III (moderate water quality) status; while river waters at logging area (Mukah) found under Class IV (slightly polluted). The most influence variables that cause the deteriorating of water quality is moderately low dissolved oxygen; high concentration of ammonia nitrogen; biochemical oxygen demand; chemical oxygen demand; major ion and trace metals; and nearly acidic pH. This study also revealed that due to conversion of tropical forest into various land use; water quality had deteriorated significantly as was evident from variation of water quality variables. Independent sample test (t-test) showed that the selected physico-chemical variables varied significantly from disturbed and undisturbed forest (P<0.05). Whereas one-way ANOVA showed that the selected physico-chemical variables varied significantly from locations (P<0.05); and both found high at disturbed forest. The ANOVA illustrated that the water quality progressively deteriorated from upstream to downstream areas. Pearson correlation revealed the facts that all the physicochemical variables of river water correlated to some or the other ways. Any deterioration to one variables; will cause deterioration to other variables. The PCA results revealed that 87.30% of the total variance was explained by five factors, that is, organic and inorganic (42.96%), salinity factors (22.11%), organic pollution (dissolved and suspended material) (8.61%), waste water pollution from agricultural and organic load (7.07%) and erosion factor (6.56%) that represents total variance of waters quality in the disturbed forest. Overall these results highlight the sensitivity of river water towards quality changes respectively, which may be altered as a result of both, extensive land management and natural ecosystem disturbances. Conversion of natural tropical forest to other land uses to generate negative impacts and severely affects the forest waters quality. Balancing the needs of growth and protecting forest usually has a large effect on water quality and should be a priority.